Rainfed cultivation with supplemental irrigation modelling on seed yield and oil of Coriandrum sativum L. using precision agriculture and GIS moisture mapping - Agathos Filintas (IWA Publishing, 2021)
The aim of the present study was to determine the effects of rainfed and supplemental irrigation, and sowing period (SP) treatments on coriander (Coriandrum sativum L.) yield, essential oil content and umbel heights by applying new agro-technologies (TDR-sensors for soil moisture (SM), geographical information system (GIS), precision agriculture, soil-hydraulic analyses and geostatistical models) for yield and SM root zone geospatial modelling and two-dimensional GIS mapping. Results of laboratory analysis indicated a suitable soil for coriander's growth and revealed that field's soil was characterized sandy clay loam (SCL) with mean values: soil organic matter (SOM) = 1.70%, bulk specific gravity = 1.42 g·cm−3, plant available water = 0.129 cm·cm−1, pH = 7.10 and cation-exchange capacity (CEC) = 19.3 cmol·kg−1. The two-way ANOVA statistical analysis (P = 0.05) results revealed that the irrigation treatments (IR1: rainfed, IR2: rainfed plus supplemental irrigation [best]), and the SP treatments (SP1: October's last week, SP2: November's first week [best]) significantly affects coriander's seed yield and essential oil content, but the SP have no significant effect on plant's umbel height (P = 0.873). Supplemental irrigation, using a limited amount of water, if applied during the critical crop growth stages, can result in substantial improvement on seed yield (+284.934%), essential oil content (+125.396%) and plant's umbel height (+117.929%). HIGHLIGHTS Supplemental irrigation, if applied during the critical crop growth stages (Lmid and Llate), can result in substantial improvement on coriander's seed and essential oil yields.; Daily monitoring with TDR sensors, 2-D TDR-GIS geostatistical mapping of soil's moisture root zone profile and calculation of the soil-water-plant-atmosphere balance, can outcome better decisions for supplemental irrigation which is an effective response to alleviate the adverse impact of soil moisture stress during dry spells.; The significance of the results is strongly indicating that farmers should adopt these practices (supplemental irrigation, November sowing, 2-D GIS moisture monitoring and precision agriculture mapping) in order to achieve better management decisions and yields, environmentally friendly agricultural management and increased income.; In the future, modern farms will work differently in order to be more profitable, primarily because of advancements in technology, such as soil, water and crop sensors, new devices, drones and robots, farm machines and information technology.;